MENGGALI NILAI-NILAI KEPEMIMPINAN PADA BUDAYA JAMBI MELALUI CERITA PUTRI RENO PINANG MASAK - Fitriana, Desi; Berliana, Fadhilla; Nilam Sari, Ayu; Agustian, Fajar; Liyani, Rusta; Wiwin Margiati; Alena, Mareta; Aulia Fikri, Rivaldi; Athif Razani Widayat, Muhammad; Luthfi Arrazaq, Muhammad; Ridho Patra Wardana, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
n the midst of globalization, folk tales such as Putri Reno Pinang Masak are starting to be displaced by popular culture which does not always reflect local values. The younger generation tends to be less familiar with this story, so they miss the opportunity to learn from the moral values and leadership contained in it. This research aims to explore leadership values in Jambi folklore, namely the story of Putri Reno Pinang Masak. The method used in this research is a historical method which includes five main stages: topic selection, source collection, source verification, data interpretation, and historical writing. The sources used are literature, articles and historical documents relevant to the folklore of Putri Reno Pinang Masak. The research results show that the story of Putri Reno Pinang Masak contains very important leadership values, such as love for the people, wisdom in making decisions, courage to face threats, integrity, responsibility, and the ability to maintain honor and self-respect. The folklore of Putri Reno Pinang Masak contains various leadership values that are important and relevant to be applied in today's life. These values can be used as inspiration in forming a strong leader's character, especially in facing challenges and making wise decisions. Keywords: jambi culture, folklore, leadership values